Analysis and design of website-based hospital management information system applications - Helmina Helmina; Zulfikri Akbar; Muhammad Ikhsan; Rian Dani; Shandy Amandha (Institute of Computer Science (IOCS), 2023)
This study aims to create a hospital management information system application, Hospital Management Information System (SIMRS), at KH Daud Arif Kuala Tungkal Hospital. Currently, KH Daud Arif Hospital in providing services are still carried out manually, starting from registration, meeting the doctor, and taking medicine, up to the payment/cashier stage, so it takes a long time, resulting in less than optimal completion of ongoing management. The method used is the Waterfall Method. This model provides a sequential approach to software life flow starting from the analysis, design, coding, testing and support stages. This Hospital Management Information System (RSIM) can increase the efficiency and effectiveness of hospital operations and assist in managing information and data related to patients, staff, and hospital activities. Also to optimize hospital operations, improve patient care, and provide greater benefits to medical staff, patients, and hospital management and can help automate and speed up hospital administration processes, such as patient registration, appointment scheduling, payments, and inventory management.